Isaiah's Suffering Servant Before and After Christianity - Brettler, Marc Zvi 1958-; Levine, Amy-Jill 1956- (2019)
The so-called "Suffering Servant" of Isaiah 52:15-53:12 takes on new meaning in each of his settings, from the exilic or early post-exilic community of Deutero-Isaiah, to the repurposing of this figure by the author of Daniel, mid-second century BCE during the persecutions of Jews by Antiochus IV Epiphanes, through the numerous New Testament citations of and allusions to Jesus as fulfilling Isaiah's predictions concerning this servant, and on to several post-biblical Jewish understandings of this enigmatic figure. In showing how and why the servant receives such numerous readings, we demonstrate both how readers across the centuries and within different traditions understand Isaiah through their own circumstances, and why Jews and Christians should respect each other's readings rather than attempt to "prove" the truth of one tradition on the basis of a specific understanding of prophecy.
Keywords: Book of; Isaiah; Jesus; Jewish-Christian relations; Prophecy; Reception History; Suffering Servant